Analisa Perencanaan Lumpur Pemboran Menggunakan HPWBM pada Sumur “E” Lapangan “P” - Prastio, Eko (Fakultas Teknik, Universitas Bhayangkara Jakarta Raya, 2022)
The “E” well to be drilled is a development well in the “P” field located in the North Sumatra Basin. During the drilling operation in well “E” using HPWBM, HPWBM is used to overcome shale instability. This water-based mud is used because it is cheaper and more economical than using oil-based mud. However, this mud needs to be added with other chemicals because HPWBM has a weakness in controlling shale formation. The mud system design for the “E” well uses the offset well method, which uses data from nearby wells for comparison. Well “E” is divided into two intervals. Hole interval 12 1/4